Business Assistance Strategy Through the BESTE Program to Increase the Resilience of BTPN Syariah Customers' Micro Businesses in the Sapuran Area, Wonosobo - Hartanti, Wulan Siska Dwi; Oktafia, Renny; Nisa, Fauzatul Laily (Pascasarjana Universitas Mataram, 2025)
The MSME mentoring program in the Sapuran area, Wonosobo, aims to empower underprivileged communities with a focus on micro businesses. This assistance uses an Assets-Based Community Development (ABCD) approach which maps and develops existing assets in the community, supporting business sustainability. Mentoring involves student facilitators who work with 30 customers from grocery, agricultural, goods production and reseller businesses. The methodology applied consists of four stages: SWOT analysis, providing material on business management, marketing and brand development, material review, and direct practice. The ABCD approach encourages customers to utilize internal resources, such as existing skills, products and networks, to design innovative solutions for their businesses. The results of the assistance show that customers better understand how to manage their business in a structured and efficient manner, as well as increasing product competitiveness through the use of simple technology, such as marketing via social media and developing a business identity. This program also strengthens community economic resilience through strengthening micro businesses and becomes a model that can be applied in other regions to support the sustainability of MSMEs